Technologies for sewer rehabilitation in Malaysia - Gupta, B.S.; Chandrasekaran, S.; Ibrahim, S. (Pipeline Publications Australia, 2005)
After assuming control of Malaysia’s sewer systems, Indah Water Konsortium Sdn Bhd commissioned a study into the available sewer rehabilitation techniques in the market with the intention of finding suitable methods to rehabilitate sewers in and around Malaysia. This report outlines the key findings of the study, focusing on the applicable sewer rehabilitation techniques which use Trenchless Technology.